Overview of Printing Wearable Antenna - Mahadzir, M. A.; Hassan, Nurhafizzah; Khirotdin, Rd Khairilhijra'; Ngadiron, M. F. (Journal of Fundamental and Applied Sciences, 2018)
The usage of wearable textiles in antenna section has been seen increased due to the advanced in miniaturization of wireless devices. A wearable antenna is meant to be a part of the clothing and body used for communication purposes, which includes tracking and navigation, mobile computing and public safety. Printing of conductive ink gives the leisure of flexibility properties on electronics thus allowing it to be used on conformal surfaces such as textiles. However, the current printing techniques mostly suffer from ink incompatibility and limited of substrates to be printed with. Hence, this paper discusses an overview of conventional and current printing techniques of wearable antenna and a potential of automatic syringe deposition system to print electronics structure mainly antenna using conductive ink on conformal substrates particularly textiles.